Penentuan Kapasitas Adsorpsi Maksimum dan Energi Adsorpsi Herbisida Paraquat (1,1’-Dimetil-4,4’-Bipiridilum Diklorida) pada Tanah Pertanian - Syahrial Syahrial (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Determination of Paraquat (1,1,-Dimethyl-4,4’-Bipyridilium Dichloride) Maximum Adsorption Capacity and Adsorption Energy on Farm SoilABSTRACT. The purpose of this research to determination of paraquat (1,1,-Dimethyl-4,4’-Bipyridilium Dichloride) maximum adsorption capacity and adsorption energy. Maximum adsorption capacity and adsorption energy were predicted by Gibbs free energy, G. The paraquat adsorption to show reversible properties and therefore Gibbs free energy can determinate by equilibrium constant, K. Maximum adsorption capacity were 18,811 mg/g (0,000101 mol/g) and Gibbs free energy was -25360 kJ/mol for 1100C soil.